2015
DOI: 10.1097/mca.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shockwave myocardial therapy is efficacious in improving symptoms in patients with refractory angina pectoris – a multicenter study

Abstract: Objective Medically refractory angina remains a significant health concern despite major advances in revascularization techniques and emerging medical therapies. We aimed to determine the safety and efficacy of extracorporeal shockwave myocardial therapy (ESMT) in managing angina pectoris. Methods A single-arm multicenter prospective study was designed aiming to determine the safety and efficacy of ESMT. Patients of functional Canadian Cardiovascular Society class 11–IV, despite stable and optimal medical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
1
23
1
1
Order By: Relevance
“…(2010) [31]Placebo controlled844.7±16.250.5±16.2WtVainer J. et al (2012) [63]Single arm508.2±3.29.6±3.8MinutesKazmi W.H. et al (2012) [71]Controlled4312.2±7.820.1±15.7MinutesYang P. et al (2012) [79]Randomized, Placebo controlled25339.44±83.3427.9±63.3MetersWang Y. et al (2012) [24] b Randomized, controlled31344.3±106.4434.3±99.7MetersSchmid J.P. et al (2013) [78]Randomized, Placebo controlled1191.2±29.194.1±35.2WtPrinz C. et al (2013) [66]Single arm4378±5390±46WtCassar A. et al (2014) [27] Single arm15319.8±157.2422.1±183.3SecondsZhao L. et al (2015) [74] b Randomized, controlled32343.9±85.0489.4±72.2SecondsPrasad M. et al (2015) [68]Single arm111252.1±51.6 c 313.5±164.3Seconds457.0±146.8 d 606.0±126.4Kaller M. et al (2015) [49]Single arm1693±44101±41WtCai HY. et al (2015) [30]Single arm26360.7±116.8434.2±86.3MetersNirala S. et al (2016) [73]Controlled41336.7±120.5445.8±172.4MetersVainer J. et al (2016) [70]Single arm337.4±2.88.8±3.6Minutes

All valuables presented as mean ± SD, a valuable presented as mean ± SE, SE calculated into SD using standard formulas; b grou...

…”
Section: Resultsmentioning
confidence: 99%
“…(2010) [31]Placebo controlled844.7±16.250.5±16.2WtVainer J. et al (2012) [63]Single arm508.2±3.29.6±3.8MinutesKazmi W.H. et al (2012) [71]Controlled4312.2±7.820.1±15.7MinutesYang P. et al (2012) [79]Randomized, Placebo controlled25339.44±83.3427.9±63.3MetersWang Y. et al (2012) [24] b Randomized, controlled31344.3±106.4434.3±99.7MetersSchmid J.P. et al (2013) [78]Randomized, Placebo controlled1191.2±29.194.1±35.2WtPrinz C. et al (2013) [66]Single arm4378±5390±46WtCassar A. et al (2014) [27] Single arm15319.8±157.2422.1±183.3SecondsZhao L. et al (2015) [74] b Randomized, controlled32343.9±85.0489.4±72.2SecondsPrasad M. et al (2015) [68]Single arm111252.1±51.6 c 313.5±164.3Seconds457.0±146.8 d 606.0±126.4Kaller M. et al (2015) [49]Single arm1693±44101±41WtCai HY. et al (2015) [30]Single arm26360.7±116.8434.2±86.3MetersNirala S. et al (2016) [73]Controlled41336.7±120.5445.8±172.4MetersVainer J. et al (2016) [70]Single arm337.4±2.88.8±3.6Minutes

All valuables presented as mean ± SD, a valuable presented as mean ± SE, SE calculated into SD using standard formulas; b grou...

…”
Section: Resultsmentioning
confidence: 99%
“…9 Research works demonstrated that activation of Wnt/β-catenin signaling enhances myogenesis, 10 increases myoblast proliferation, and enhances muscle growth, 11,12 whereas, it has been reported that Wnt/β-catenin signaling can be activated by mechanotransduction. 13,14 Low-intensity extracorporeal shockwave therapy (Li-ESWT) is one example of a mechanical force that has been employed for many years to treat musculoskeletal disorders, 15 ischemic heart disease, 16,17 and vasculogenic ED. 18,19 We previously reported that Li-ESWT activated penile stem cells 20,21 and very recently, we have applied Li-ESWT effectively to improve SUI.…”
Section: Introductionmentioning
confidence: 99%
“…Other limitation of the current study is the lack of a sham arm, making it difficult to exclude the partial placebo effect. However, those benefits were associated and supported by objective data such as the improvement in SPECT/CT perfusion score demonstrated in other studies …”
Section: Discussionmentioning
confidence: 59%
“…However, those benefits were associated and supported by objective data such as the improvement in SPECT/CT perfusion score demonstrated in other studies. 18,19,24 It is important to note that CSWT is still an experimental therapy, with very few patients currently treated with this modality compared with other strategies used in refractory angina, and its long-term prognosis still remains unknown. A longer follow-up and the assessment of long-term effect on quality of life in a large randomized study should be considered.…”
Section: Limitationsmentioning
confidence: 99%